2015
DOI: 10.1007/s10140-015-1351-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CT compared to ultrasound in the evaluation of acute abdominal pain in children younger than 10 years old

Abstract: To assess the diagnostic value of ultrasound compared to CT in evaluating acute abdominal pain of different causes in children 10 years of age and under, hospital records and imaging files of 4052 patients under age of 10 who had imaging for abdominal pain were reviewed. One-hundred-thirty-two patients (3 %), (74 males/58 females) who underwent ultrasound and CT within 24 h were divided by age: group I, ages 0-48 months (25 patients); group II, 49-84 months (53 patients); and group III, 85-120 months (54 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is allowed to diagnose children appendicitis by CT scan in our country and Simanovsky N et al had reported non-diagnostic or equivocal US in the evaluation of acute abdominal pain in children younger than 10 years old is probably sufficient to justify the additional CT radiation burden [ 38 ]. CT scanning had been done in most young children because the ultrasonic diagnosis was uncertain, little experience existed with the nonoperative treatment of APA, and the effect of an appendicolith on clinical outcomes was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is allowed to diagnose children appendicitis by CT scan in our country and Simanovsky N et al had reported non-diagnostic or equivocal US in the evaluation of acute abdominal pain in children younger than 10 years old is probably sufficient to justify the additional CT radiation burden [ 38 ]. CT scanning had been done in most young children because the ultrasonic diagnosis was uncertain, little experience existed with the nonoperative treatment of APA, and the effect of an appendicolith on clinical outcomes was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Ultrasound was found to be sufficient to confirm or rule out a surgical condition in approximately 97% of cases. 84 Using ultrasound as the primary imaging modality in children with suspected acute appendicitis has been shown to be cost-effective and to reduce the number of CT scans ordered 82,85,86 without resulting in inferior outcomes. 87,88 However, in some situations a definitive diagnosis cannot be made by ultrasound, requiring further evaluation with CT or MRI.…”
Section: Head Ctmentioning
confidence: 99%
“…It must, however, be acknowledged that ultrasound also has many benefits as a diagnostic tool. For example, according to a recent study, ultrasound alone can exclude or confirm 97% of abdominal surgical conditions in children under 10 years . Another study found ultrasound to be diagnostic in 48% of paediatric patients with acute abdominal pain .…”
Section: Discussionmentioning
confidence: 99%